Multi-Sensor Evaluating Effects of an Ecological Water Diversion Project on Land Degradation in the Heihe River Basin, China - Song, Xiang; Liao, Jie; Xue, Xian; Ran, Youhua (Frontiers in Environmental Science, 2020)
To deal with the increasingly severe land degradation in the downstream of the Heihe River Basin(HRB) in northwest China, an Ecological Water Diversion Project(EDWP) was implemented since 2000. A comprehensive analysis of the effects associated with the project on land degradation is necessary. According to the concept of Land Degradation Neutrality (LDN), multi-sensor data has been used to extract information on Land Use/Land Cover (LULC), aeolian desertification, and vegetation dynamics, which were chosen as monitoring indices to reveal the process of land degradation in the HRB. Then, these results were combined with meteorological data, socio-economic statistics, and hydrological data to discuss the main driving factors influencing the land degradation process to evaluate the effects of the EWDP on land degradation in the HRB. The results showed that the process of land degradation in the HRB could be divided into two stages, in which the degradation trend was dominant from 1990 to 2000, and the rehabilitation trend was dominant from 2000 to 2015. Although both climate variation and human activities have been favorable to land degradation development in the HRB, climate factors have no significant influence on land degradation in the midstream and downstream in the HRB. The decrease of available water resources is the dominant driving factor of a series of ecological environment problems in the downstream of the HRB, and the land degradation process of the HRB has been stopped and reversed mainly attributed to the EWDP. The EWDP facilitated the recovery of the deteriorated ecosystem by improving the efficiency of surface water resources reallocation in the downstream. Still, the EWDP indirectly led to the sink of the groundwater table in the midstream with resulting in local vegetation degradation.